Review on Zeolite Mesoporous Structure: To Keep Nutrient for Fertilizer Purposes - Azmi, Amiratul Husna; Harun, Zawati (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Reduction in crop production and plant growth is one of the major problems faced by the agriculture industry. This problem can be solved by increasing the nutrient uptake of the plants with the addition of zeolite additive that able to hold the nutrient within its mesoporous structure. The ability of zeolite not only can trap nutrient within microporous structure but also provide cation exchange mechanism that will better improve the ion diffusivity and absorption. Hence, this study will do a review on the synthesis factor of zeolite, the characteristic properties mesoporous structure of zeolites and its ability to keep nutrient for fertilizer purposes. The main raw material is kaolin that will be discussed and focused with different composition and the synthesis method of zeolite will focusing more on hydrothermal synthesis technique. Few parameters and results from previous author’s findings will be discussed and analyzed further in this study. The focused parameters were heating temperature, NaOH concentration and Si/Al ratio to determine the CEC and crystallinity of zeolite type A.